Analisis Kurikulum dan Pola Pembelajaran Akidah Akhlak Tingkat Madrasah Ibtidaiyah Kelas Rendah pada Kurikulum 2013 - Syarip Hidayatullah (Program Pascasarjana UNU Surakarta, 2023)
The 2013 curriculum has been well-designed to respond to the challenges and demands of the 21st century. However, it is deemed necessary to carry out an analytical study to obtain a comprehensive new perspective to achieve its objectives. The purpose of this research is to get the right perspective in implementing the curriculum in low-class MI. This research is library research with a descriptive-analytical approach. The results of the analysis show: First, the 2013 Curriculum in the Aqidah Akhlak subject for the lower grades of Madrasah Ibtidaiyah with integrated thematic material is appropriate and psychologically and philosophically appropriate. Second, learning patterns with a scientific approach are characteristic of this curriculum, but an emphasis on Contextual Teaching Learning (CTL) is needed to help students interact with the real world and evaluate learning with authentic and comprehensive assessments.